2019
DOI: 10.1155/2019/5769147
|View full text |Cite
|
Sign up to set email alerts
|

Study on Transmutation of Minor Actinides as Burnable Poison in VVER-1000 Fuel Assembly

Abstract: Thermal reactors have been considered as interim solution for transmutation of minor actinides recycled from spent nuclear fuel. Various studies have been performed in recent decades to realize this possibility. This paper presents the neutronic feasibility study on transmutation of minor actinides as burnable poison in the VVER-1000 LEU (low enriched uranium) fuel assembly. The VVER-1000 LEU fuel assembly was modeled using the SRAC code system, and the SRAC calculation model was verified against the MCNP6 cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Therefore, Am-241 is more likely to capture neutron, and consequently transmute the fastest. This result is consistent with previous studies in other type of reactors [10,11].…”
Section: Ma Incinerationsupporting
confidence: 94%
See 2 more Smart Citations
“…Therefore, Am-241 is more likely to capture neutron, and consequently transmute the fastest. This result is consistent with previous studies in other type of reactors [10,11].…”
Section: Ma Incinerationsupporting
confidence: 94%
“…This efficiency only accounts for fissioned MA, not considering MA isotopes that were transmuted instead of fissioned. The efficiency is not too dissimilar with other references [11,24], but the required time was around twice as long.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…In nuclear reactor, transmutation can be performed in both research reactor [17,18] and power reactor with various types of fission reactors. Conventional light water reactors (LWRs) have been studied to transmute TRU, either by using TRU wholly as a fuel rod [6,[19][20][21] or as coating layer [7,22]. Combining TRU with thorium ensures negative yield of TRU [23], due to the reason mentioned previously.…”
Section: Introduction mentioning
confidence: 99%
“…In a previous study [17], the feasibility of MA transmutation in VVER-1000 LEU fuel assembly [18] as burnable poison was studied and the results showed that the total MA transmutation rate of ~20% could be obtained. However, only the MA vector of the VVER-440 spent fuel was considered.…”
Section: Introductionmentioning
confidence: 99%